Dy3+ doped tellurite glasses for solid-state lighting: An investigation through physical, thermal, structural and optical spectroscopy studies - Kibrisli, O.; Ersundu, A. E.; Ersundu, M. Celikbilek (ELSEVIER, 2019)
In the present work, a series of Dy3+ ion doped tellurite glasses in the (50-x)TeO2-25WO(3)-25Li(2)O-xDy(2)O(3) system were synthesized using conventional melt quenching technique to investigate colorimetric and radiative properties of Dy3+ ions in a new and stable host for their evaluation as solid-state lighting materials. Physical and structural properties were studied through density calculations, refractive index measurements, and Fourier transform IR spectroscopy analysis. Thermal properties of glasses -glass transition (T-g) and crystallization (T-c/T-p) temperatures and temperature difference (Delta T) - were determined using differential scanning calorimetry. Optical absorption spectra of glasses were recorded with Vis-NIR spectrophotometer. CIE color coordinates, correlated color temperature, color rendering index and yellow to blue emission intensity ratio values were obtained through photoluminescence analysis. Radiative properties such as, radiative transition probability, stimulated emission cross-section, branching ratio and optical bandwidth gain were calculated according to Judd-Ofelt theory. The obtained optical spectroscopy results were found to be comparable or better than other reported glass systems. From the derived results, glasses with Dy3+ ion concentration lower than 0.5 mol% were found to show the closest CIE color coordinate values to pure white light and highest CCT and CRI values revealing good potentiality to be used for applications in white LEDs and solid-state lasers.
Keywords: Dy3+ ion; Tellurite glass; White LED; Photoluminescence; Judd-Ofelt analysis; ALUMINO-BORATE GLASSES; WHITE-LIGHT; ENERGY-TRANSFER; ELECTRONIC POLARIZABILITY; PHOTOLUMINESCENCE PROPERTIES; LUMINESCENCE PROPERTIES; FLUOROBORATE GLASSES; EMISSION PROPERTIES; PHOSPHATE GLASSES; OXYFLUORIDE GLASS; Materials Science